Michiel van Groesen (ed.), The Legacy of Dutch Brazil - Noorlander, D.L. (BMGN - Low Countries Historical Review, 2015)
Michiel van Groesen (ed.), The Legacy of Dutch Brazil (New York: Cambridge University Press, 2014, x + 363 pp., isbn 978 11 07 06117 0).